Cost-effectiveness of high-dose quadrivalent influenza vaccine versus standard-dose quadrivalent influenza vaccine for older people in a country with high influenza vaccination rate - Eliel Nham; Hye Seong; Hakjun Hyun; Jin Gu Yoon; Ji Yun Noh; Hee Jin Cheong; Woo Joo Kim; Eugene Kim; Leejung Choi; Jung-Min Lee; Joon Young Song (Human Vaccines & Immunotherapeutics)
The highdose quadrivalent influenza vaccine (QIVHD) has shown improved protection against influenza and its complications in older adults. We aimed to evaluate the costeffectiveness of QIVHD compared with QIVSD among Korean adults aged ≥ 65 years in reducing influenzarelated disease burden. We evaluated the 2016/2017 and 2017/2018 seasons and their average values using a static decision tree model. The difference in efficacy between standard-dose (SD) and high-dose (HD) was calculated based on the results of a clinical trial comparing Fluzone® High-Dose Vaccine and Fluzone® Vaccine in older adults. Incremental cost-effectiveness ratios (ICERs) were assessed from the healthcare system perspective. A discount rate of 4.5% was applied to life-year-gained (LYG) values and utilities. We performed deterministic and probabilistic sensitivity analyses to account for both epidemiological and economic sources of uncertainty. In the analysis of the 2017/2018 season, the QIV-HD strategy generated an excess of 0.00182 life-years (Lys)/person and 0.003953 quality-adjusted life-years (QALYs)/person compared with QIV-SD. The ICER was 6,467.56 United States Dollars (USD)/QALY. In the analysis from the 2016/2017 season, QIV-HD caused a surplus of 0.00117 Lys/person and 0.003272 QALYs/person compared with QIV-SD. ICER was 7,902.46 USD /QALY. From the average data of the 2016/2017 and 2017/2018 seasons, an excess of 0.00147 Lys/person and 0.003561 QALYs/person were generated using QIV-HD compared with QIV-SD, while the ICER was 7,190.44 USD /QALY. From the healthcare system perspective, QIV-HD was a more cost-effective vaccination option in reducing influenza-related disease burden and healthcare costs in Koreans aged ≥ 65 years compared with QIV-SD.